Pengaruh Beban Kerja Terhadap Kinerja Karyawan dengan Kelelahan Emosional Sebagai Mediator pada Perguruan Tinggi Islam di Jawa Tengah - Astri Normalita Sari; Muhammad Sholahuddin (Syntax Idea)
The aim of this research is to analyze the influence of workload on employee performance with emotional exhaustion as a mediating variable at Islamic Universities in Central Java. This type of research is quantitative research. The data collection technique used is a questionnaire with variable measurement using a Likert scale for each statement developed from the variable indicators. The sample in the study amounted to 93 respondents. The sampling technique is purposive sampling. The data analysis technique in this research uses Structural Equation Modeling (SEM) SmartPls 4.0. The results of the research show that: 1) There is a negative and significant direct influence between workload on employee performance for employees of Islamic Universities in Central Java. 2) There is a positive and significant direct effect between workload on emotional exhaustion in employees of Islamic Universities in Central Java.